Apoptosis reduces both the in vitro replication and the in vivo infectivity of a baculovirus. - Clem, R J (1993)
Apoptotic programmed cell death occurs when the insect cell line SF-21, derived from Spodoptera frugiperda, is infected with mutants of the baculovirus Autographa californica nuclear polyhedrosis virus (AcMNPV) which lack a functional p35 gene. However, infection of the Trichoplusia ni TN-368 cell line with p35 mutants does not result in apoptosis (R. Clem, M. Fechheimer, and L. Miller, Science 254:1388-1390, 1991). We have examined the effect of apoptosis on AcMNPV infections in cell lines and larvae of these two insect species. Production of viral progeny was significantly lower in SF-21 cells infected with p35 mutants than in cells infected with wild-type (wt) or revertant viruses. Viral gene expression was abnormal in SF-21 cells infected with p35 mutants; there was a delay in the transcription and translation of early and late viral genes, a lack of expression of very late genes, and a total cessation of protein synthesis late in the apoptotic process. In vivo analysis revealed that the dose of budded virus required for 50% lethality in S. frugiperda larvae was approximately 1,000-fold higher for p35 mutants than for wt or revertant viruses. In contrast, the replication and infectivity of p35 mutant viruses was equivalent to that of wt AcMNPV during infection of both TN-368 cells and T. ni larvae. Thus, the data indicate that a host apoptotic response provides protection against viral infection at the organismal level and that the p35 gene constitutes a host range determinant for AcMNPV infection.